Radioembolization for the Treatment of Hepatocellular Carcinoma: The Road to Personalized Dosimetry and Ablative Practice - De la Garza-Ramos, Cynthia; Toskich, Beau B. (Seminars in Interventional Radiology, 2021)
Radioembolization dosimetry for the treatment of hepatocellular carcinoma has evolved alongside our understanding of best practice for this therapy. At the core of advances in dosimetry are personalized and ablative applications of radioembolization, which have generated paradigm shifts in both safety and efficacy. This review provides a summary of fundamental radioembolization dosimetry concepts and narrates how our approach to treating patients has shifted from conventional to tailored and definitive therapy.
Keywords: radioembolization; Y90; dosimetry; liver cancer; interventional radiology